1998
DOI: 10.1136/vr.143.2.52
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution of Ornithobacterium rhinotracheale in experimentally infected turkeys

Abstract: FIG 1: (a) Sagittal section of the head showing soft tumour tissue in which the premolar and molar teeth were loosely embedded (arrows). (b) Radiograph of the left mandible showing severe cortical bone destruction and much lysis of the ramus and body of the mandible. There was destruction of alveolar bone with displacement of caudal cheek teeth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 6 publications
1
3
1
Order By: Relevance
“…Group (2) infection with ORT alone show nasal discharge, coughing and reduce appetite during first week post-infection, while group (3) broilers infected with ORT and treated with lincospectine 1g/L 5 successive days showed decrease mortality and morbidity. The result are in agreement with other ptrviously cited studies (Hafez et al, 1993 andBack et al, 1996).…”
Section: Results Of Pathogenicity Of Local Isolates Ort To Broiler Ch...supporting
confidence: 93%
“…Group (2) infection with ORT alone show nasal discharge, coughing and reduce appetite during first week post-infection, while group (3) broilers infected with ORT and treated with lincospectine 1g/L 5 successive days showed decrease mortality and morbidity. The result are in agreement with other ptrviously cited studies (Hafez et al, 1993 andBack et al, 1996).…”
Section: Results Of Pathogenicity Of Local Isolates Ort To Broiler Ch...supporting
confidence: 93%
“…Both the IT and IV IR of our model allowed the successful study of O. rhinotracheale induced lesions as was noted in previously reported experimental models (van Empel et al, 1996;Sprenger et al, 1998;van Veen et al, 2000b;Eroksuz et al, 2006;Kiliç et al, 2009;Walters et al, 2014), but, importantly, our study achieved the successful experimental inoculation of both BH and NH phenotypes of O. rhinotracheale by two IR in broiler chickens in order to clarify differences in pathogenicity for the first time. Furthermore, our experimental model contrasted with the absence of experimentally induced lesions in turkeys previously reported by Back et al (1998). Our experimental model highlighted the direct association between the inoculation routes and the organs affected.…”
Section: Discussioncontrasting
confidence: 42%
“…In broiler flocks, 68% (13/19) had been found positive, and this was higher than the 60% positive flock found in southern Brazil (8) and the 26% found in broiler flocks in Germany (20). The high prevalence of positive broiler flocks may be because of the continuous introduction of the agent from their parent flocks (6,30). The results revealed that age might influence the seroprevalence of ORT in Thailand.…”
Section: Discussionmentioning
confidence: 99%